2015
DOI: 10.17344/acsi.2015.1590
|View full text |Cite
|
Sign up to set email alerts
|

Improving Drinking Water Quality by Remineralisation

Abstract: The reason of low mineral content in source water is its origin in poorly soluble mineral geological structures. There are many areas with very soft low-mineralised water around the world. All people involved in drinking water treatment as well as some public health experts and producers of chemicals used for water treatment may be interested in the study. Enrichment of drinking water by minerals including calcium and magnesium is very important particularly in regions where drinking water is prepared by desal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Although not explicitly recommended in the literature, it appears that it may be advantageous to implement a CaCO 3 -MgO blend rather than using CaMg(CO 3 ) 2 . For example, Luptáková and co-workers found that magnesium content dominated in treated water when using half-calcined dolomite and suggested the use of dolomite with higher Ca content for more balanced effluent target values [91]. However, dolomite is known to be naturally more heterogeneous than limestone [92].…”
Section: Water Treatment Applicationsmentioning
confidence: 99%
“…Although not explicitly recommended in the literature, it appears that it may be advantageous to implement a CaCO 3 -MgO blend rather than using CaMg(CO 3 ) 2 . For example, Luptáková and co-workers found that magnesium content dominated in treated water when using half-calcined dolomite and suggested the use of dolomite with higher Ca content for more balanced effluent target values [91]. However, dolomite is known to be naturally more heterogeneous than limestone [92].…”
Section: Water Treatment Applicationsmentioning
confidence: 99%
“…Surface and groundwater are the main sources of drinking water worldwide, and purification processes that increase safety and quality of drinking water are of a crucial importance. 1 The presence of emerging substances (ESs) in the environment has become a subject of growing interest in recent decades. ESs are defined as materials present at low concentrations in the environment that have a potential or actual risk to the "One Health" trilogy -environment, human and animal.…”
Section: Introductionmentioning
confidence: 99%
“…Different processes and different carbonate rocks are used for RC of drinking water, mostly under CO 2 saturation. In particular, flow-through systems are used where carbonate rock is added to a flow-through device based on various filters, through which the entire treated water flows (Haney & Hamann 1969;Al-Rqobah & Al-Munayyis 1989;Olejko 1999;Withers 2005;Luptáková & Derco 2015).…”
Section: Introductionmentioning
confidence: 99%